Experiences of Mothers on Parenting Children with Leukemia - Cornelio, Sheryl Jyothi (Indian J Palliat Care, 2016)
INTRODUCTION: Childhood cancer is the leading cause of death among children. Leukemia is one of the most common childhood cancers. OBJECTIVE: The objective of this study was to explore the experiences of mothers on parenting children with leukemia. MATERIALS AND METHODS: A qualitative approach with phenomenological design was used. To collect depth information from the mothers of children with leukemia, purposive sampling technique was adopted. Data were collected from ten mothers. Semi-structured interview schedule was used to collect the data. Data were analyzed using Husserl's method. RESULT: The themes derived are the pivotal moment in life, the experience of being with a seriously ill child, having to keep distance with the relatives, overcoming the financial and social commitments, responding to challenges, experience of faith as being key to survival, health concerns of the present and future, and optimism. CONCLUSION: The study concluded that chronic illness such as leukemia in children results in negative impact on the child and on the mother.